Vascular Endothelial Growth Factor (VEGF) Serological and Lacrimal Signaling in Patients Affected by Vernal Keratoconjunctivitis (VKC) - Marcella Nebbioso; Andrea Iannaccone; Marzia Duse; Michele Aventaggiato; Alice Bruscolini; Anna Maria Zicari (Journal of Ophthalmology)
Background. Vernal keratoconjunctivitis (VKC) is a rare inflammatory disease involving the ocular surface, with seasonally exacerbated symptoms. Both type-1 and type-4 hypersensitivity reactions play a role in the development of VKC. Purpose. The aim of the present study was to assess the presence and evaluate the concentration of the vascular endothelial growth factor (VEGF) in tear and blood samples from patients with VKC, during the acute phase, based on the histopathological vasculostromal structure of the tarsal papillae. Methods. Two groups of children aged between 6 and 16 years of life were enrolled: 21 patients (16 males, 76%) affected by VKC, tarsal or mixed form, and 13 healthy children (5 males, 38%) used as controls. Blood and tear samples were obtained from all patients, in order to specifically assess the presence of VEGF. Statistical analyses were performed with one-way ANOVA, followed by post hoc comparisons with the Bonferroni tests. Pearson’s correlation was chosen as statistical analysis to assess the relationship between the expression levels of VEGF in tears and blood and the clinical parameters measured. Results. Comparing the 2 groups for VEGF concentration, a statistically significant difference was found in tear samples: the mean value was 12.13 pg/mL (±5.54 SD) in the patient group and 7 pg/ml (±4.76 SD) in controls (p<0.05). However, no statistically significant difference was found when comparing VEGF concentration in blood samples (p>0.05), with a mean value of 45.17 pg/mL (±18.67 SD) in VKC patients and 38.08 pg/mL (±19.43 SD) in controls. Conclusions. This pilot study highlights the importance of lacrimal and vascular inflammatory biomarkers that can be detected in VKC patients during the acute phase, but not in healthy children. The small group of patients warrants additional studies on a larger sample, not only to further investigate the role of VEGF but also to evaluate the angiogenic biomarkers before and after topical treatment.